Analysis of Generic Competency Development Strategies for the Medan SAR Team in Facing Disaster Management Challenges - Nabila, Mutia Putri; Zainarti; Nuri Aslami (Pendidikan Administrasi Perkantoran, Universitas Negeri Makassar, 2024)
This article aims to explore the strategies for developing generic competencies implemented by the Medan SAR Team in facing the challenges of disaster management. By combining internal data from the Medan SAR Team and interviews with relevant personnel, this study reveals the efforts made by the Medan SAR Team to enhance preparedness for various types of disasters. The analysis of generic competency development strategies focuses on several key aspects, such as training in communication skills, teamwork, and problem-solving, which play a crucial role in improving the team's readiness to respond to disasters. This research emphasizes the importance of generic competency development as an integral part of an effective disaster management strategy. By identifying challenges, analyzing existing strategies, and providing recommendations for performance improvement, this article is expected to strengthen their capacity to respond to emergency situations quickly, efficiently, and effectively.